Analysis of Actantial Model in Suzanne Collins’ "The Hunger Games" - Dzikriya, Uliya (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
This study aims to analyze plot structure in Collins’ The Hunger Games. There are several questions that researcher wants to find, what the elements of plot are, how do the elements of plot compose the plot structure of the story, and what kind of plot is applied in the novel. This study is a qualitative analysis by applying A.J. Greimas approach. The data were collected by reading, identifying, interpreting and analyzed using the approach and theories which used in this study by using actants. The result of this study were the elements of plot consist of beginning, problem of the story, rising action, climax, falling action, and resolution. To find out the main plot structure, this study classifies the function of each character into six actants, they are sender, receiver, subject, object, helper and opponent. Finally, the researcher concluded what kind of plot and how the ending of the novel is. The plot of the novel is dramatic or cronological plot because the story through in chronological order. In addition, the novel is closed plot because the problem of the story is solved. Keywords: Actant, Greimas, Plot, Sructuralism